Copper‐Catalyzed Reduction of Alkyl Triflates and Iodides: An Efficient Method for the Deoxygenation of Primary and Secondary Alcohols1. (4th December 2013) - Dang, Hester; Cox, Nick; Lalic, Gojko
Abstract We describe an effective method for catalytic reduction of 1° alkyl sulfonates, and 1° and 2° iodides in the presence of a wide range of functional groups. This Cu‐catalyzed reaction provides a means for the effective deoxygenation of alcohols, as demonstrated by the highly selective reduction of 1° alcohols using a triflation/reduction sequence. A preliminary study of the reaction mechanism suggests that the reduction does not involve free‐radical intermediates.